Performance of mode-locked pulses in thulium-holmium-doped fiber lasers induced by paraffin-layered TiO2–Nb2CTx composite - Ahmad, H.; Rusni, N.A.M.; Samion, M.Z.; Yusoff, N.; Zaini, M.K.A.; Mayzan, M.Z.H.; Thambiratnam, Kavintheran; Mahmoodin, Z. (Springer, 2025)
The paraffin-coated TiO2–Nb2CTx MXene composite saturable absorber (SA) significantly advances ultrafast fiber laser technology. By synergizing the non-linear optical properties of the TiO2–Nb2CTx MXene composite SA with the protective coating of paraffin, this novel SA demonstrates superior performance compared to its uncoated counterpart. The coated SA achieves an enhanced modulation depth of 19.5%, improved energy efficiency, and exceptional mode-locked pulse stability with a signal-to-noise ratio (SNR) of 69.3 dB. The mode-locked pulses generated using the paraffin-coated SA exhibits a pulse width of 1.64 ps and a 3-dB spectral bandwidth of 3.4 nm. The uncoated SA produces a broader pulse width of 2.02 ps and a narrower 3-dB bandwidth of 1.9 nm. These results indicate that incorporating paraffin enhances the non-linear optical response of the SA, thereby broadening the spectral bandwidth and facilitating the generation of shorter pulses. Also, the paraffin-coated SA delivers 1.21% laser efficiency, outperforming 1.07% of its uncoated counterpart. Furthermore, the paraffin layer provides robust environmental resistance, shielding the material from moisture, oxidation, and contamination, dramatically extending operational stability from 4 h to 1 month. This innovation addresses critical limitations of conventional SAs, including limited durability, environmental sensitivity, and fabrication complexity.